THE OPTIMIZATION OF THE REACTOR BLOCK OPERATING PARAMETERS OF UNIT WITH A SOLID HEATING AGENT - A. A. Selivanov; O. V. Afanaseva; A. N. Mrakin; G. K. Zhanaev; A. Yu. Kamaev (Известия высших учебных заведений: Проблемы энергетики)
In the article the questions of optimization of technological parameters of mutual functioning of the system of apparatuses of the reactor block of semi-coking of slate with a solid heating agent (UTT) are considered.